Effects of Metaldehyde and Niclosamide on the Behavior and Reproductive Capacity of Radix Quadrasi Von Moellendorf (Basommatophora: Lymnaeidae) - Bambang Retnoaji (Universitas Gadjah Mada, 2003)
The effects of molluscicides exposure, metaldehyde and niclosamide, on the behavior and reproductive capacity of Radix quadrasi was studied under laboratory conditions. R quadrasi were exposed to different concentration-rates of niclosamide: 0, 0.045, 0.058 and 0.075 mg/L, and of metaldehyde: 0, 100, 112 and 130 mg/L. The symptoms of poisoning of treated snails were observed closely throughout the duration of the experiment. Observations were made three times: at the beginning of treatment (0 hour), 12 hours, and 24 hours after exposure. The surviving R. quadrasi were maintained for one month to determine their reproductive capacity. Results indicated that there was immediate reaction of the snails to molluscicide exposure. Lower concentration-rates of molluscicide triggered water-leaving behavior. Such behavior occurred in all of the low and medium concentration-rates of niclosamide and metaldehyde, as well as in some snails from the control group. By contrast, higher concentration-rates caused almost instantaneous immobility. Niclosamide and metaldehyde also significantly reduced the reproductive capacity of R. quadrasi. The number of egg masses and eggs laid varied with the treatments. However, the incubation period of the treated eggs was not statistically different from the treated ones. This study showed that both niclosamide and metaldehyde significantly affected the behavior and reproductive capacity of the R. quadrasi. Between the two molluscicides used in this experiment, niclosamide was more toxic than metaldehyde.